Making educational planning: skills, methodologies, experiences - Orefice, Carlo; Guraziu, Erina (Form@re - Open Journal per la formazione in rete, 2018)
The ability to design effective educational interventions requires education and training professionals to deal with methodological, institutional and experiential issues. Through the first of these plans they develop the basic teaching skills to write, start and manage a project; with the second they face the organizational and management dynamics to develop a network project with public and third sector services; finally, the last plan helps them to expand their skills in supporting projects in complex and differentiated contexts. In this perspective, the theme of educational planning is therefore of strategic importance in supporting the profile of the L19 educator, which in the synthesis proposed by the authors appears as a professional able to build a project, share it with institutional stakeholders and implement it in dynamic conditions and constantly evolving. Fare progettazione educativa: competenze, metodologie, esperienze La capacità di progettare interventi educativi efficaci impone ai professionisti dell’educazione e della formazione di confrontarsi sul piano metodologico, istituzionale ed esperienziale. Attraverso il primo di questi piani essi sviluppano le competenze didattiche fondamentali per scrivere, avviare e gestire un progetto; con il secondo affrontano le dinamiche organizzative e gestionali per sviluppare un progetto in rete con i servizi alla persona pubblici e del terzo settore; l’ultimo piano infine li aiuta ad ampliare le proprie capacità nel sostenere progetti in contesti complessi e differenziati. In tale prospettiva il tema della progettazione educativa riveste una importanza strategica nel sostenere il profilo dell’educatore della L19, che nella sintesi proposta dagli Autori appare come un professionista in grado di costruire un progetto, condividerlo con gli stakeholder istituzionali ed attuarlo in condizioni dinamiche e in continua evoluzione.